The Criminalization of LGBQ/GNCT Youth, California, 2014 - Irvine, Angela ([Verlag nicht ermittelbar], 2018)
The researchers examined sexual-orientation and gender conformity disparities in criminalization for prostitution. The specific purpose of this study was to explore the links between family rejection, homelessness, child welfare involvement, and prostitution charges for youth in the justice system.